Experimental investigation of wing with vortex generators - Ударцев, Є.П.; Щербонос, О.Г. (Proceedings of National Aviation University, 2010)
The idea of research of the organized vortex flow of a wing for the purpose of perfection of aerodynamic characteristics on the big angels of attack develops. The wing with vortex generators in the form of flows on a forward edge in low velocity wind tunnel was with that end in view investigated. It is shown, that the organized vortex flow of a wing with vortex generators on a forward edge practically does not change aerodynamic characteristics at small angels of attack and strongly influences on the big angels of attack, increasing the maximum elevating force and improving momentum characteristics at small change of drag.